People, Places and Culture - Kola-Lawal, Constance Omawunmi (Nigeria, 2016)
An exiting journey on Nigeria with over 100pages of caprivating images and information. Discover the people, places and culture of this beautiful land...
Keywords: Community; Juvenile Literature; Nigeria; People, Places & Culture